Studies on Old High German syntax : left sentence periphery, verb placement and verb-second - Axel, Katrin (Linguistik aktuell, 2007)
This monograph is the first book-length study on Old High German syntax from a generative perspective in twenty years. It provides an in-depth exploration of the Old High German pre-verb-second grammar by answering the following questions: To what extent did generalized verb movement exist in Old High German? Was there already obligatory XP-movement to the left periphery in declarative root clauses? What deviations from the linear verb-second restriction are attested and what do such phenomena reveal about the structure of the left sentence periphery? Did verb placement play the same role in s.